The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/genomea.01422-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Lymantria dispar multiple nucleopolyhedrovirus Isolated in Southwestern Poland

Abstract: We report here the complete genomic sequence of Polish alphabaculovirus isolated from dead gypsy moth caterpillars. Its genome structure and G+C content indicate that it is a Lymantria dispar multiple nucleopolyhedrovirus (LdMNPV) strain which possesses the shortest sequence among eight other (similar to reference sequence AF081810) LdMNPV sequences available in GenBank; it is 159,729 bp long.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The vef -1 gene is also absent in LdMPNV-3041 (Japan) [ 22 ], which is close to our isolate LdMNPV-J2 (Japan) in the phylogenetic analysis of Harrison et al [ 25 ]. In addition, the isolates LdMNPV-RR01 (Poland) [ 42 ], LdMNPV-Nsk-07 (Russia) (MK411292), and LdMNPV-27/0 (Russia) [ 43 ] also lack a vef -1 gene. In the NCBI database, the complete genomes of the other isolates, LdMNPV and LdMNPV-J2, were examined, and it was found that the mucin-like protein is one, but the LdMNPV-H2 and LdMNPV-T3 isolates have two of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…The vef -1 gene is also absent in LdMPNV-3041 (Japan) [ 22 ], which is close to our isolate LdMNPV-J2 (Japan) in the phylogenetic analysis of Harrison et al [ 25 ]. In addition, the isolates LdMNPV-RR01 (Poland) [ 42 ], LdMNPV-Nsk-07 (Russia) (MK411292), and LdMNPV-27/0 (Russia) [ 43 ] also lack a vef -1 gene. In the NCBI database, the complete genomes of the other isolates, LdMNPV and LdMNPV-J2, were examined, and it was found that the mucin-like protein is one, but the LdMNPV-H2 and LdMNPV-T3 isolates have two of this gene.…”
Section: Discussionmentioning
confidence: 99%